Web-based interactive media model for character building education - Benny, Benny; Fios, Frederikus; Ying, Yi; Yang, Edwin (Journal of Education and Learning (EduLearn), 2025)
This research aims to describe the learning innovation from character building learning through the Religious Moderation 360 website. The website's content includes photos of places of worship taken with a 360 camera. The research method used is phenomenology with a qualitative approach aimed to i) explain web-based learning and ii) gather student opinions on web-based learning. Data collection was done by distributing self-administered questionnaires. The research stage began with a trial questionnaire to determine the validity of the content and substance of the questions to 20 students. The valid questionnaire was distributed to 195 students from Department of Computer Science, International Business Management (IBM), and International Relations who adhere to Islam, Christianity, Hinduism, Buddhism, Confucianism, and other religions. The data gathered from the questionnaire accommodated the students’ expectations of innovation in learning religion character building. The conclusion from this research is that respondents found the developed website interesting, the audio-visual material innovative, they felt motivated to learn, and were interested in learning about other religions through the website. Future research is expected to explore various opinions of religious leaders and places of worship that are the result of acculturation from various countries. Thus, learning religion also involves learning about culture.